Exploring the Antimicrobial Activities of Chrysophyllum albidum Seed oil in Pharmaceutical and the Seeds in Food industry. - Iyabo Oluremi Olabanji; Emmanuel Olugbenga Akinkunmi; Nancy Aniki O; Sunday Michael Arowosegbe; Olukayode Solomon Ajayi; Reuben Yoade; Funmilola Fasesan (Journal of Food and Pharmaceutical Sciences, 2021)
The anti- microbial activity tests of the seed oil, NaOH and ash soaps of the seed oil, of C.albidum were carried out to determine their effectiveness against gram+, gram– bacteria and some fungi strains. The proximate analysis of C.albidum seeds was performed to determine its nutritional benefits to mankind. Agar diffusion tests using Disc diffusion for the pure oils and soaps while the cup plate test method for dilutions was used in the determination of in-vitro activities. Standard methods as described by AOAC, (1990); AOAC, (1984) and Kjeldahl method described by Chang (2003) were used for proximate determinations. The results show the activity of the oil against Klebsiella pneumonia at a concentration as low as 10 mg/ml. The ash-soap of the leaves shows the highest antimicrobial activities because its MIC is the closest to the standard, Streptomycin. It possesses activity against Escherichia coli and Klebsiella pneumonia at a concentration as low as 5mg/ml. The % proximate analysis composition shows Moisture content, Ash content, Crude Fibre, fat/Oil, Protein, Carbohydrates as follows (14.98, 1.90, 2.09, 2.38, 12.14 and 67.65)%. The study concluded by unleashing the great potential of Chrysophyllum albidum seeds as a useful raw material in food, cosmetics and pharmaceutical industries rather than being regarded as waste in the environment